Relationship between energy consumption and economic growth in 30 countries in Europe : panel - Stjepanović, Saša (Array, 2018)
In this paper, we study the link between energy consumption and economic growth for the thirty surveyed countries in Europe. Although there are many articles on this topic, the difference between them and this one is that we study countries that have not yet been studied together. The variable that is used for consumption is the final energy consumption, which includes the consumption of all forms of energy. In this paper, we use panel data analysis that studies the connections based on the methods of fixed effect. The data used were collected from European databases, Eurostat. Based on the results of the panel data regression, we can conclude that there is a strong correlation between the observed variables. What is needed for further research is to study the correlation between variables in the long and short-term. Equally interesting would be to study the way of integration with countries that have their power sources and those that do not.